Intratracheal Poly(I:C) Exposure Accelerates the Immunological Disorder of Salivary Glands in Sjogren's-Like NOD/ShiLtJ Mice - Hu, Peng; Ming, Bingxia; Wu, Xuefen; Cai, Shaozhe; Tang, Jungen; Dong, Yuanji; Zhou, Tianshu; Tan, Zheng; Zhong, Jixin; Zheng, Fang; Dong, Lingli (Frontiers in Medicine, 2021)
Evidences have suggested that Sjogren's syndrome (SS) is associated with viral infection. The aim of this study was to investigate the involvement of respiratory viral poly(I:C) in the pathogenesis of SS and potential mechanisms using a SS-like NOD/ShiLtJ (NOD) mouse model. 5-week female NOD mice were intratracheally administered poly(I:C) every other day for 5 times to mimic viral infection. Pilocarpine induced saliva secretion was determined every 8 days. Submandibular glands (SMG) and lungs were harvested for the detection of pathological changes. We found that intratracheal administration of poly(I:C) significantly advanced and enhanced the reduction of saliva flow rate in NOD mice. Furthermore, poly(I:C) treatment aggravated the histopathological lesions and inflammatory cells infiltration in SMG. Accompanied by elevated expression of IFN cytokines and IL-33, Th1 activation was enhanced in SMG of poly(I:C)-treated NOD mice, but Th17 cells activation was unchanged among the groups. In addition, intratracheal poly(I:C) exposure promoted the expression of IL-33 and increased T cells proportion in the lung, which were consistent with the change in SMG. Therefore, intratracheal poly(I:C) exposure aggravated the immunological and function disorder of SMG in NOD mice.